ANALISIS VALIDITAS RELIABILITAS TINGKAT KESUKARAN DAN DAYA BEDA PADA BUTIR SOAL UJIAN AKHIR SEMESTER GANJIL MATA PELAJARAN MATEMATIKA KELAS XII IPS DI SMA NEGERI 12 BANDAR LAMPUNG TAHUN AJARAN 2014/2015 - Susanto, Hery; Rinaldi, Achi; Novalia, Novalia (Al-Jabar: Jurnal Pendidikan Matematika, 2015)
This study aims to(1) determinethe items quality of odd semesterfinal examin social class XII mathematics subject academic year 2014/2015 in terms of validity, reliability, level of difficulty, and distinguishing power, (2) createa program shape for calculating validity, reliability, level of difficulty and distinguishing power. The researchused quantitative descriptive method and documentation technique. The datas consisted of 128 students’ answer sheetsin social class XII academic year 2014/2015. The datas were analyzed by using several formulas of validity, reliability, level of difficulty, distinguishing powerand the use of IBM SPSS Statistics22 software and anates V4 software. The results showed that 22 questions (55%) were valid and 18 questions (45%) were invalid. The reliability of items was quite good where the reliability coefficient value more than rtabel was 0.558 based on three formulas which were Anova Hoyt, Cronbach alpha and IBM SPSS Statistics 22. The difficulty level of items was not good because the items balances including easy, medium and difficult were not proportional, the proportional balance was 3-5-2 or 3-4-3. The distinguishing power of items showed that 1 item (2.50%) was very good, 9 items (22.50%) were good, 10 items (25%) were moderate, 14 items (35%) were less good and 6 items (15%) were bad. In addition to the above results, this study also resulted a program shape to facilitate the calculation of item analysis. The program calculations are the validity index analysis, reliability, level of difficulty and distinguishing power of test instrument.